Financial Performance Analysis at KSP Balo'ta Tana Toraja 2019-2023 - Werlin Patattan; Adryanus Paridy; Benyamin Mongan (Journal of Marketing Management and Innovative Business Review, 2025)
Abstract: This study aims to analyze the financial performance of the Savings and Loan Cooperative (KSP) Balo'ta in Makale, Tana Toraja over the 2019–2023 period. A descriptive quantitative method was applied using secondary data from annual financial reports. The analysis employed financial ratios—liquidity, solvency, activity, and profitability—to evaluate the cooperative's condition and its ability to sustain operations. Results indicate that KSP Balo'ta maintained a strong liquidity position throughout the study period. Although solvency ratios declined due to increased reliance on external funding, profitability showed significant improvement in the final year. Activity ratios also revealed efficient asset management. These findings offer strategic input for strengthening capital structure and financial management amid economic fluctuations, including the impact of the COVID-19 pandemic. The study contributes to the development of cooperatives as resilient and adaptive community-based financial institutions. Keywords: financial performance, savings and loan cooperative, liquidity ratio, profitability ratio, COVID-19 pandemic.